Thyroid and Bone Remodeling Markers in Premenopausal and Postmenopausal Women: A Multivariate Machine Learning Approach - Thakur, Rajesh Kumar; Dhakal, Rojiya; Joshi, Govardhan; Bista, Pabitra; Khadka, Anil; Khanal, Sudip; Acharya, Aashish; Gautam, Sujan; Lamichhane, Anit; Bhatt, Mahendra Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Menopause induces significant hormonal shifts that may impact thyroid function and bone metabolism. This study aimed to compare thyroid profile (FT3, FT4, and TSH) and bone remodeling (serum calcium, phosphorus, and ALP) markers between premenopausal and postmenopausal women and to examine their predictive ability via multivariate and machine learning methods. Method: This cross-sectional study was performed among 178 women (89 premenopausal, 89 postmenopausal) attending Manmohan Memorial Teaching Hospital (MMTH), Kathmandu, Nepal. Serum levels of FT3, FT4, TSH, calcium, phosphorus, and ALP were estimated using standard methods. Statistical analyses were carried out by using Mann‒Whitney U tests, Spearman correlations, MANOVA, PCA, ANCOVA, and classification models such as logistic regression, LDA, SVM, and random forest. Result: Postmenopausal women had markedly higher TSH and ALP levels, wereas lower serum calcium and phosphorus levels. MANOVA revealed a significant multivariate effect of menopausal status (Wilks’λ= 0.6818, p <0.001). Furthermore, the data were analyzed via machine learning models such as PCA, logistic regression and random forest. PCA revealed partial group separation. Among the different classification models, random forest performed better, with 81% accuracy, whereas LDA and logistic regression attained 78% accuracy. ALP and serum calcium were the most discriminative features. ANCOVA revealed that age, rather than menopausal status, significantly predicted calcium levels. A partial correlation confirmed a positive association between FT4 and calcium independent of age. Conclusion: Menopausal status significantly affects the levels of thyroid and bone remodeling markers. ALP and calcium serve as strong discriminators of the menopausal state. Integrating endocrine and bone biomarkers with multivariate and machine learning models improves diagnostic insight into menopause-related physiological changes.